Hypopigmented Mycosis Fungoides with Large Cell Transformation in a Child. Issue 5 (14th August 2017) - Pradhan, Dinesh; Jedrych, Jaroslaw J.; Ho, Jonhan; Akilov, Oleg E.
Abstract: Hypopigmented mycosis fungoides (HMF) is the most common variant of mycosis fungoides (MF) in children. Large‐cell transformation in HMF has never been reported. Herein we report a case of HMF in an 8‐year‐old boy who presented with a 6‐year history of hypopigmented patches on the bilateral arms, lower back, buttocks, posterior thighs, and lower legs. Biopsy revealed an abnormal CD8 + epidermotropic T‐cell infiltrate consistent with the diagnosis of MF. The T‐cell clonality study was positive. The patient was started on narrowband ultraviolet B (NBUVB) phototherapy and topical steroids. He had a 50% reduction in his patches after 10 months of treatment, after which he developed a single annular plaque on his left thigh. The biopsy specimen demonstrated large cells that were diffusely CD8 + and CD30 − . Clobetasol propionate ointment was prescribed, which led to complete resolution of the plaque within 2 weeks. NBUVB phototherapy was continued and the patient had a complete response within the following 5 months. The case is an example of exceptionally rare large‐cell transformation in pediatric MF and stresses the importance of regular follow‐up of these patients.